Network monopoly / Tan Kean Yeap - Tan , Kean Yeap (2002)
The number of computers in use worldwide, according to the International Data Corporation, is in excss of 100 milion. Moreover, because of the expanding memory anda processing power of these computers, users can put the machine to work on new kinds of applications and functions. Accordingly, the pressure from the users of these systems for ways to communicate among all these machines is irresistible. The demand for connectivity is manifested in many areas. one such area is about the creation of dynamic network entertainment. Multiple-party gaming is a fascinating and multifaced topic to beresearched on. This thesis steps towards developing a netv orked board game, supporting multiple players. The main aspect of this thesis is to produce a network monopoly system, which process multiple game sessions concurrently, enabling users to play the graphical game with people within the network. The algorithm design and implementation method mustnot only be workable, but also highly efficient in terms of execution speed and respond time. With the powerful networking features of Java, it is expected that this project would produce a "real" game engine. The possible applications of multimedia-networked system are endless, as the demand to supoort interactive communication among groups of users has increased significantly. The Network solution applies in this game system permits only low level of communication, particulary of sending and receiving limited amount of messages within network. The category of networking could serves to be a small foundation from which to base the future scenario of other reliable multicast and real-time web based gaming system.